Second order Linear Differential Equations of Fuchsian Type with Four Singularities - Lukashevich, N.A. (Нелінійні коливання, 2001)
We study a system of linear singularly perturbed functional differential equations by the method of integral manifolds. We construct a change of variables that decomposes this system into two subsystems, an ordinary differential equation on the center manifold and integral equations on the stable manifold.